Juice for Florida’s Future - Jude Grosser (EDIS, 2022)
It’s no secret that the recent season in Florida was a disaster, with record low production and terrible fruit quality due to HLB.  Juice Brix and soluble solids were so low that harvest was delayed in many groves, resulting in fruit on the ground, even with Valencia.  Most people have concluded that Hamlin has no future in Florida’s future juice industry, but what is a viable replacement?  How does our beloved Florida orange juice industry climb out of this hole?  The UF-CREC Citrus Breeding Team believes that new scion and rootstock cultivars, combined with improved production systems and enhanced nutrition is the way forward.  Here we focus on new sweet orange and sweet orange-like selections in our breeding pipeline with good potential to improve our juice products, and help to restore our industry.